GEO-ELECTRICAL MAPPING OF BEACHROCK IN VATERA BEACH, LESVOS - Meligonitis, R.; Galanopoulos, D.; Hasiotis, T.; Velegrakis, A. (Bulletin of the Geological Society of Greece, 2016)
Beachrock (Br) is encountered on the coastal zones, playing an important but also complex role in their morphodynamic evolution. Although Br has been widely studied, two important issues require further investigation. The first concerns the importance of the interaction of the dynamically changing coastal environment with the temporal changing surficial and underground hydrogeological balance. The second has to do with the spatial distribution and the evolution of Br with respect to the specific “host” coastal zone geo environment. This paper designates the electrical resistivity method as a tool that contribute in arguing in the abovementioned issues. The research comprised subsurface measurements with the DC resistivity method along two profiles located on Vatera beach (Lesvos Island), where there is a significant Br outcrops. Twelve geoelectric soundings were carried out using the Axial Pole-Dipole electrode array. The electrical resistively measurements permitted an indirect estimation of TDS, which depicts the coastal interface of fresh water - sea water. The interpreted geoelectric model shows two thin formations attributed to Br. The first is the inland extension of the Br outcrop and the second it is believed to be a primary stage of Br build up.